Candida tropicalis burn wound sepsis: A series of histopathology-confirmed cases. (June 2018) - Fan, Chunjie; Tian, Qingfen; Huang, Guobao; Zhang, Lei; Wu, Qiuhe; Zhang, Keyan
Abstract: Fungal infection in severely burned patients is a serious problem due to various factors, such as the extensive application of antibiotics. In this study, we report on the course of severely burned patients with Candida tropicalis burn wound sepsis. Five such cases were reviewed. The patients were treated with itraconazole intravenously and simultaneous antibiotics to prevent bacterial infections. In addition, dermabrasion was used to excise the eschar and the wound surface was covered immediately with dermatoplasty. Meanwhile, the skin necrosis related to the fungal infection was removed. The wound surfaces of all five patients were healed well and the parameters of laboratory examination went back to normal. We assume that prompt diagnosis and timely treatment including extensive debridement of necrosis, antifungal drugs, and antibiotics were the key points leading to favourable outcome.